Technology Use Attitudes of Teachers in the Field of Special Education - Dalbudak, İbrahim (2021)
Information and communication technologies are extremely effective in the education of children with autism, that is, in special education, just as they are a part of our lives and affect all areas of our lives. This study was made to determine the attitudes of the teachers in the field of special education towards these technologies. 124 teachers among the teachers in the field of special education working in İzmir province participated in the study voluntarily. In the study, “Personal Information Form” and “Information and Communication Technologies Attitude Scale” developed by Günbatar (2014) to determine the level of information and communication technologies use of teachers in the field of special education were used. The data obtained were evaluated in the SPSS 23 package program. In analyzing the data, ANOVA and t-test were used for the general scale among the “Mann Whitney U” and “Kruskal Wallis 1 Way ANOVA” tests. In addition, in cases where significant differences exist, the scales at which the differences occur were determined by using “Dunn’s Nonparametric Comparison” for subscales and “Tukey Post Hoc” test for general scale. As a result of the findings obtained, there is a significant difference as the age of teachers changes and according to that they have special students do sports, sports are effective on special students according to their gender, there is no significant difference according to the persistence of the knowledge that special students want to be taught while playing games, and according to their status of finding technological opportunities sufficient. As a result, we can say that as teachers’ attitudes towards technology are positive, students with or without disabilities can learn information in a short time.